Applications of optogenetic and chemogenetic methods to seizure circuits: Where to go next?. Issue 12 (9th August 2017) - Forcelli, Patrick A.
Abstract: Epilepsy is the quintessential circuit disorder, with seizure activity propagating through anatomically constrained pathways. These pathways, necessary for normal sensory, motor, and cognitive function, are hijacked during seizures. Understanding the network architecture at the level of both local microcircuits and distributed macrocircuits may provide new therapeutic avenues for the treatment of epilepsy. Over the past decade, optogenetic and chemogenetic tools have enabled previously impossible levels of functional circuit mapping in neuroscience. In this review, examples of the application of optogenetics and chemogenetics to epilepsy are raised, the comparative strengths and weaknesses of these approaches are discussed for both preclinical and translational applications, and recent applications of these approaches in other areas of neuroscience are highlighted. These points are raised in an effort to highlight the potential of these methods to address additional unanswered questions in epilepsy.